An individualised approach to reduce trocar site hernia - Zukiwskyj, Marianna; Daniel E. Cattanach (International Surgery Journal, 2023)
In systematic reviews, the calculated pooled prevalence of trocar site hernia (TSH) has been estimated at 0.5%. Increasing age, high body mass index, smoking, and wound infection potentially influence the incidence. Increasing trocar size, retrieval of specimens through trocar sites, excessive force used in manipulation of the trocar and frequent re-insertion of the trocar may also play a role in the enlargement of the muscolofascial defects. This paper reports a case of a Richter’s hernia within a 5 mm abdominal port site occurring in the early post operative period following laparoscopy. This is significant because it is an uncommon complication of a common procedure. We highlight that various factors may increase the likelihood of this uncommon condition, and provide a brief overview of TSHs.